Application of systemic treatment in conversion therapy options for liver cancer - Bei, Haoyang; Mai, Weiheng; Chen, Weifeng; Li, Mingyi; Yang, Yongguang (Frontiers in Oncology, 2022)
Radical hepatectomy is the main treatment method to improve the prognosis of patients with intermediate and early-stage liver cancer. Most liver cancer patients in China are in an advanced stage at the time of initial diagnosis, losing the opportunity for surgical treatment. Therefore, it is particularly important to down-stage unresectable liver cancer to resectable liver cancer clinically, which is an important way to improve the survival of patients and also a hotspot of current clinical research. In recent years, with the increase of effective treatment methods for liver cancer, the resection rate of conversion surgery for unresectable advanced liver cancer has been significantly improved, and a growing number of patients benefit from conversion therapy. This article mainly reviews the connotation of conversion therapy for liver cancer, the patient selection, the selection of conversion strategy, the timing of sequential operations, the scheme and safety, etc.